Analisis Laporan Keuangan Perbandingan Kinerja Keuangan Perusahaan Manufaktur di Indonesia : (Studi pada Perusahaan Intan Wijaya International, Duta Pertiwi Nusantara, dan Madusari Murni Indah Periode 2019-2023) - Ayu Asari; Aliatus Nurrochmah; Septiana Rozzi Rahmawati; Cholis Hidayati (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
This study compares the financial performance of three manufacturing companies in Indonesia, namely PT Intan Wijaya International Tbk, PT Duta Pertiwi Nusantara Tbk, and PT Madusari Murni Indah Tbk, during the 2019-2023 period. The analysis was conducted using liquidity, activity, solvency, profitability, and market ratios to evaluate the financial health of each company. The results show that PT Duta Pertiwi Nusantara Tbk excels in liquidity ratios (average current ratio of 3.92 and average quick ratio of 3.48) as well as operational efficiency on average age of receivables (46.06 days) and inventory turnover (17.68 times). Meanwhile, PT Madusari Murni Indah Tbk has the highest solvency ratio (average TIE of 48.2% and average Fixed Charge Coverage of 8.2), although its debt-to-asset burden is also greater (debt ratio of 33%). On the other hand, PT Intan Wijaya International Tbk performed best on profitability (average ROE of 61.4%) and effectiveness of total asset utilization (average total asset turnover of 0.91). However, all three companies face the challenge of ratio fluctuations due to the impact of the COVID-19 pandemic. This study is expected to provide important insights for stakeholders in making strategic decisions, as well as contribute to the literature of financial performance analysis of the manufacturing sector.